Rekrutmen Pendidik dan Tenaga Kependidikan dalam Penempatan Kerja di SD IT Ma’arif Padang Panjang Sumatra Barat - Nailis Saadah; Jamilus Jamilus (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2024)
This research aims to understand the recruitment system for educators and educational staff at SD IT Ma'arif Padang Panjang. The method used in this research is qualitative with a descriptive qualitative design. The subject of this research is the Staff of Wakaf Ma'arif Foundation Padang Panjang. Data collection is conducted through method triangulation, where data in the form of relevant documents obtained from the website and school files, then the accuracy of the documents is checked through interviews. The results of this research indicate that the recruitment, selection, and placement process at SD IT Ma'arif Padang Panjang adopts a one-stop approach. The initial steps involve identifying and analyzing the needs of educators and educational staff, followed by the foundation's announcement of job vacancies, administrative selection, written tests, Quran reading tests, psychological tests, and interviews. Subsequently, the results of the interviews are analyzed, and the announcement of accepted applicants is made. Afterward, the process of job placement, issuance of employment contracts, and a three-month training program are carried out.